2006
DOI: 10.2136/sssaj2005.0216
|View full text |Cite
|
Sign up to set email alerts
|

Maize Root Biomass and Net Rhizodeposited Carbon

Abstract: Assessment of net primary productivity of maize (Zea mays L)‐based agroecosystems is dependent on both above and belowground dry matter production that is ultimately returned to the soil as residue and decaying roots. Root to shoot ratio (R/S) is a parameter often used to estimate root biomass (RB) when shoot biomass is measured or estimated. The labor intensive nature of root sampling and wide variety of sampling techniques has lead to a paucity of maize RB data in the literature, and few researchers have end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
134
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(146 citation statements)
references
References 87 publications
9
134
2
1
Order By: Relevance
“…The proportion for the SOC pool was similar (3.9±2.3 %) with our data (3.8 %). The metadata analysis reported by Amos and Walters (2006) found that net rhizodeposited C values for maize cultivated in growth chambers was 22.4 %, and significantly higher than that calculated NRC (ratio of net rhizodeposited C, i.e., soil microbial biomass and as soil residue, to total net root-derived belowground C, i.e., standing root biomass C+rhizodeposited C) for the emergence, elongation, heading and grainfilling stages in this study (i.e. 0.13, 0.13, 0.11 and 0.26, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion for the SOC pool was similar (3.9±2.3 %) with our data (3.8 %). The metadata analysis reported by Amos and Walters (2006) found that net rhizodeposited C values for maize cultivated in growth chambers was 22.4 %, and significantly higher than that calculated NRC (ratio of net rhizodeposited C, i.e., soil microbial biomass and as soil residue, to total net root-derived belowground C, i.e., standing root biomass C+rhizodeposited C) for the emergence, elongation, heading and grainfilling stages in this study (i.e. 0.13, 0.13, 0.11 and 0.26, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…13 C-and 14 C-isotope labeling studies have revealed the complex dynamics of photoassimilate routing during the growth cycles of cereal crops (see review by Kuzyakov and Domanski 2000). However, most studies used plants at early stages of maturity (less than 60 days after emergence) which may have caused under-or overestimation of C allocation to different soil pools because of changes in plant physiology during the growth cycle (Hütsch et al 2002;Kuzyakov and Schneckenberger 2004;Amos and Walters 2006;Jones et al 2009). For example, root respiration is decreased under mature plants (Kuzyakov 2006), when resources are diverted to reproduction and fruiting (Dungait et al 2011), and the proportion of C translocated belowground and used for root growth, respiration and exudation decreases (Swinnen et al 1994).…”
mentioning
confidence: 99%
“…5 is modified from Jonas et al 2004) can be stimulated by the mycorrhiza (Tarafdar and Marschner 1995;Osorio and Habte 2001). The P solubilization occurs in the rhizosphere soil where organic compounds are released by roots or mycorrhizae (Nguyen 2003;Amos and Walters 2006). Many rhizosphere microorganisms are heterotrophs and might use these organic substrates to produce organic acids, which would increase P concentrations in solution (Hameeda et al 2006;Reyes et al 2006).…”
Section: Effect Of Inoculation On Plant Growth Under Salt Stressmentioning
confidence: 99%
“…According to the review by Amos and Walters (2006) we can assume a net belowground carbon deposition (root biomass and rhizodeposition) of 29 ±13% of shoot (= stover) biomass carbon for maize at physiological maturity. From the data on stover yield in Table 3 we can therefore estimate the belowground carbon deposition was 757 ± 344 kg OC ha −1 a −1 in the fertilized plots.…”
Section: Estimates Of the Belowground Input Of New Maizederived Orgamentioning
confidence: 99%
“…From the data on stover yield in Table 3 we can therefore estimate the belowground carbon deposition was 757 ± 344 kg OC ha −1 a −1 in the fertilized plots. Taking into account that root/shoot ratios increase by 41.6 ±8.6% under nitrogen deficiency (Amos and Walters, 2006), net belowground carbon deposition in the non-fertilized plots was 421 ±242 g OC ha −1 a −1 (calculated from Table 3). With a lignin concentration of 10.3% in organic carbon of maize roots (Dignac et al 2005) as a basis, the belowground lignin carbon deposition from belowground maize biomass could be estimated as 79 kg C VSC ha −1 a −1 in the fertilized plots versus 44 kg C VSC ha −1 a −1 in the nonfertilized plots (calculated from Table 3).…”
Section: Estimates Of the Belowground Input Of New Maizederived Orgamentioning
confidence: 99%